PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM TENTANG GAYA DAN FUNGSINYA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH - Yayan Rahmayantia (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2019)
IMPROVEMENT OF STUDENT LEARNING OUTCOMES IN NATURAL SCIENCE LESSONS LEARNING ABOUT THE FORCE AND FUNCTION BY USING THE LEARNING MODEL COOPERATIVE TYPE MAKE A MATCHThis study aims (1) To find out the Make a Match type of cooperative learning model can improve student learning outcomes in Natural Sciences about the force and function in class V SD Negeri Bantarjati 7, Bogor Utara, Bogor, semester 2 (2) describe the process of improving student learning outcomes in Natural Science subjects about their force and function before and after using the Make a Match type cooperative learning model in class V SD Negeri Bantarjati 7  (3) To measure the magnitude of the increase in student learning outcomes in Nature Science subjects about force and function after using the Make a Match cooperative learning model in class V of SD Negeri Bantarjati 7. The results of this study indicate that using the Make a Match cooperative learning model can be a fun variation of learning for students so that proven, men increase student learning outcomes in Class V Bantarjati State Elementary School 7. Before using the Make a Match type of cooperative learning model the learning outcomes of students only reached an average value of 62.25 then an increase occurred after using the Make a Match type cooperative learning model to 74, 12 in cycle 1 and 79.125 in cycle 2. From the description above the researchers concluded that the use of a Make a Match type of cooperative learning model adapted to learning material can create a pleasant learning situation so that an increase in student learning outcomes. Therefore the researchers suggest that the use of the Make a Match type of cooperative learning model be socialized and used as an alternative in science learning in schools within the Bogor City Education Office.